Exterior material for power storage device, and power storage device

JP2025035351APending Publication Date: 2025-03-13TOPPAN HOLDINGS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023142337
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0014】 本開示によれば、優れた水分バリア性及びラミネート強度を有し、且つ高温においても高いシール強度を有する蓄電装置用外装材及び蓄電装置を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035351000001_ABST
    Figure 2025035351000001_ABST
Patent Text Reader

Abstract

To provide an exterior material for a power storage device which has excellent moisture barrier properties and laminate strength and has high seal strength even at a high temperature, and to provide a power storage device.SOLUTION: The exterior material for a power storage device includes a substrate layer, a barrier layer, an adhesive layer, and a sealant layer in this order. The adhesive layer is formed using a resin composition which contains a resin containing an acid-modified polyolefin resin, and the resin contains a halogen. The halogen content in the adhesive layer may be 12 mass% or more and 40 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an exterior material for an electricity storage device and an electricity storage device. [Background technology]

[0002] Secondary batteries such as lithium ion batteries are widely used in portable electronic devices, electric vehicles and hybrid electric vehicles that use electricity as a power source. As a battery with improved safety compared to lithium ion batteries, all-solid-state lithium batteries that use inorganic solid electrolytes instead of organic solvent electrolytes have been studied. All-solid-state lithium batteries are safer than lithium ion batteries in that they are less susceptible to thermal runaway caused by short circuits, etc.

[0003] In all-solid-state batteries, particularly all-solid-state batteries using a sulfide-based solid electrolyte, when moisture penetrates, the sulfide-based solid electrolyte reacts with moisture to generate hydrogen sulfide. Since hydrogen sulfide is toxic, it is necessary to suppress the generation of hydrogen sulfide and, if it does occur, to quickly render it harmless (deodorize it). In order to suppress the generation of hydrogen sulfide, it has been considered to add moisture adsorbing substances such as zeolite, silica gel, and lime to each layer of the exterior material. For example, Patent Document 1 below discloses an exterior material using zeolite or the like as a moisture adsorbing substance. In addition, the applicant of the present application has already filed an application (Patent Application No. 2022-204337) using a layered compound as a substance that blocks the passage of water vapor. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-187855 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, although the packaging material described in Patent Document 1 has excellent moisture barrier properties, there is room for improvement in terms of lamination strength and seal strength at high temperatures. Also, although the packaging material described in the above application has excellent moisture barrier properties, there is room for improvement in terms of lamination strength and seal strength at high temperatures. Therefore, there has been a demand for an exterior material that has excellent moisture barrier properties and lamination strength, and also has high seal strength even at high temperatures. In addition, in power storage devices other than all-solid-state batteries, it is desirable to use an exterior material that has excellent moisture barrier properties and lamination strength, and also has high seal strength even at high temperatures, from the viewpoint of suppressing deterioration of battery performance due to moisture and improving heat resistance temperature.

[0006] The present disclosure has been made in consideration of the above-mentioned problems, and has an object to provide an exterior material for an electricity storage device, which has excellent moisture barrier properties and lamination strength, and also has high sealing strength even at high temperatures, and an electricity storage device. [Means for solving the problem]

[0007] The present disclosure provides an exterior material for an electricity storage device, comprising a base material layer, a barrier layer, an adhesive layer, and a sealant layer in this order, the adhesive layer being formed using a resin composition containing a resin that contains an acid-modified polyolefin resin, and the resin containing a halogen.

[0008] The above packaging material has excellent moisture barrier properties and lamination strength, and also has high seal strength even at high temperatures. The inventors of the present disclosure speculate as follows about the reason why the above effects are obtained. That is, since the resin contains a polyolefin resin, the adhesive layer has high crystallinity and is less permeable to water. Furthermore, since the resin contains a halogen, the adhesive layer is polarized, the intermolecular forces in the adhesive layer are increased, and the adhesive layer becomes denser. This makes the adhesive layer even less permeable to water molecules. As a result, the exterior material has excellent moisture barrier properties. Furthermore, since the adhesive layer is acid-modified, the cohesive force of the adhesive layer is increased, and the adhesion between the adhesive layer and the barrier layer and sealant layer is improved. As a result, the exterior material has excellent lamination strength and high seal strength even at high temperatures.

[0009] In the packaging material for an electricity storage device, the adhesive layer may have a content of the halogen of 12 mass % or more. In this case, the adhesive layer becomes more sufficiently densified, and the moisture barrier property of the packaging material for an electricity storage device is more sufficiently improved.

[0010] In the electrical storage device packaging material, the adhesive layer may have a halogen content of 40% by mass or less. In this case, the adhesive layer does not contain an excessive amount of halogen, so that the molecular weight of the resin contained in the adhesive layer is sufficiently large, and the sealing strength of the electrical storage device packaging material at high temperatures is sufficiently improved.

[0011] The resin composition preferably further contains a polyfunctional isocyanate compound. In this case, the acid-modified polyolefin resin reacts with the isocyanate-based adhesive, increasing the cohesive strength of the adhesive layer, thereby enabling the adhesive layer to have excellent adhesion and heat resistance, and enabling the exterior material to have high sealing strength and sufficient heat resistance.

[0012] The polyfunctional isocyanate compound more preferably contains at least an isocyanurate compound. When the resin composition contains an isocyanurate compound as a polyfunctional isocyanate compound, the adhesive layer of the exterior packaging material can have better adhesion and heat resistance than when the resin composition does not contain an isocyanurate compound, and the exterior packaging material can have higher sealing strength and heat resistance.

[0013] The present disclosure also provides an electricity storage device including a battery element and an outer bag that houses the battery element, the outer bag having the outer packaging material. According to the energy storage device of the present disclosure, the exterior material has excellent moisture barrier properties. This prevents moisture from entering the interior of the exterior bag, and the battery element is less likely to be exposed to moisture, thereby preventing a decrease in the performance of the battery element housed inside the exterior bag. In addition, the exterior material has excellent lamination strength and high sealing strength even at high temperatures, so that even when the energy storage device is used at high temperatures, the exterior bag is less likely to be damaged and a decrease in the sealing property of the exterior bag can be prevented. As a result, the life of the energy storage device can be extended. Effect of the Invention

[0014] According to the present disclosure, it is possible to provide an exterior packaging material for an electricity storage device, which has excellent moisture barrier properties and lamination strength, and also has high sealing strength even at high temperatures, and an electricity storage device. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 2] 1 is a perspective view of an electricity storage device according to an embodiment of the present disclosure. [Diagram 3] FIG. 2 is a plan view of a sample for measuring seal strength used in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations are omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0017] [Exterior materials for power storage devices] First, an exterior material for an electricity storage device according to an embodiment of the present disclosure will be described with reference to Fig. 1. Fig. 1 is a schematic cross-sectional view of an exterior material for an electricity storage device according to an embodiment of the present disclosure. As shown in FIG. 1, the exterior material for an energy storage device of this embodiment (hereinafter also simply referred to as "exterior material") 10 is an exterior material used for an energy storage device, and comprises, in this order, a base material layer 11, a first adhesive layer 12a, a barrier layer 13, a second adhesive layer 12b as an adhesive layer, and a sealant layer 16.

[0018] The exterior material 10 may have a first corrosion prevention treatment layer 14a between the substrate layer 11 and the barrier layer 13, and may have a second corrosion prevention treatment layer 14b between the barrier layer 13 and the second adhesive layer 12b. In the exterior packaging material 10, the base material layer 11 is the outermost layer and the sealant layer 16 is the innermost layer. That is, the exterior packaging material 10 is used with the base material layer 11 facing the exterior side of the electricity storage device and the sealant layer 16 facing the interior side of the electricity storage device.

[0019] The second adhesive layer 12b is formed from a resin composition for forming a second adhesive layer, the resin including an acid-modified polyolefin resin. The resin includes a halogen. The packaging material 10 has excellent moisture barrier properties and lamination strength, and also has high seal strength even at high temperatures.

[0020] Each layer constituting the packaging material 10 will now be described in detail.

[0021] <Base material layer 11> The base layer 11 provides heat resistance in the sealing process when manufacturing the electricity storage device and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for a large-scale electricity storage device, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.

[0022] The base layer 11 is preferably a layer formed of an insulating resin, such as polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenol resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, or the like.

[0023] When these resins are applied to the base layer 11, they may be in the form of a stretched or unstretched film, or in the form of a coating film. The base layer 11 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. In the case of a film, a co-extrusion film or a film laminated with an adhesive may be used. In the case of a coating film, a film coated the number of times that it is laminated may be used, and a film and a coating film may be combined to form a multilayer.

[0024] Among these resins, polyester resin and polyamide resin are preferable for the base layer 11 because of their excellent moldability. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resin include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12.

[0025] The base layer 11 may contain various additives, such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a dehydrating agent, a crystal nucleating agent, and a tackifier, as necessary.

[0026] The substrate layer 11 may be in the form of a stretched or unstretched film, or in the form of a coating film. The substrate layer 11 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. When the substrate layer 11 is a film, the substrate layer 11 may be a layer obtained by co-extrusion of multiple layers, or a layer obtained by laminating multiple layers with an adhesive. When the substrate layer 11 is a coating film, the substrate layer 11 may be a layer obtained by coating a coating liquid the number of times that the layers are laminated, or a layer obtained by combining a film and a coating film to form a multilayer may be used.

[0027] When these resins are used in the form of a film, the base layer 11 is preferably a biaxially stretched film. When the base layer 11 is a biaxially stretched film, examples of the stretching method include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep-draw formability, the biaxially stretched film is preferably one stretched by the tubular biaxial stretching method.

[0028] The thickness of the substrate layer 11 is preferably 6 to 40 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the packaging material 10 tend to be improved. When the thickness of the substrate layer 11 is 40 μm or less, the total thickness of the packaging material 10 can be reduced.

[0029] In order to suppress deformation of the base layer 11 during sealing, the melting point of the base layer 11 is preferably higher than the melting point of the sealant layer 16, and more preferably is 30° C. or more higher than the melting point of the sealant layer 16.

[0030] <First adhesive layer 12a> The first adhesive layer 12a is a layer that bonds the base layer 11 and the barrier layer 13. The first adhesive layer 12a is obtained by using a resin composition for forming a first adhesive layer. The resin composition for forming the first adhesive layer contains, for example, a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol, and a bifunctional or higher isocyanate compound (polyfunctional isocyanate compound). The above-mentioned various polyols can be used alone or in combination of two or more types depending on the function and performance required for the exterior material 10. In addition, as the resin composition for forming the first adhesive layer that forms the first adhesive layer 12a, in addition to the above-mentioned resin composition for forming the first adhesive layer, a resin composition for forming a first adhesive layer containing a base material such as an epoxy resin and a curing agent can also be used, but the resin composition for forming the first adhesive layer is not limited thereto.

[0031] The resin composition for forming the first adhesive layer may contain various additives such as flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, dehydrating agents, crystal nucleating agents, and tackifiers depending on the performance required for the first adhesive layer 12a.

[0032] The thickness of the first adhesive layer 12a is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, followability, processability, and the like, it is preferably, for example, 1 to 10 μm, and more preferably 2 to 7 μm.

[0033] <Barrier layer 13> The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the inside of the electricity storage device. The barrier layer 13 may also have extensibility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc., or metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, etc. can be used. As the film provided with the vapor deposition film, for example, an aluminum vapor deposition film or an inorganic oxide vapor deposition film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, a metal foil is preferable, and an aluminum foil is more preferable, in terms of mass (specific gravity), moisture resistance, processability, and cost.

[0034] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in terms of imparting corrosion resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.

[0035] The thickness of the barrier layer 13 is not particularly limited, but taking into consideration the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.

[0036] <First and second corrosion prevention treatment layers 14a, 14b> The first and second corrosion prevention layers 14a and 14b are layers provided to prevent corrosion of the metal foil (metal foil layer) constituting the barrier layer 13. The first corrosion prevention layer 14a prevents the barrier layer 13 from being corroded by the corrosive gas contained in the atmosphere, and also plays a role in increasing the adhesive strength between the barrier layer 13 and the first adhesive layer 12a. The second corrosion prevention layer 14b prevents the barrier layer 13 from being corroded by the electrolyte or the gas (e.g., hydrogen sulfide gas) generated inside the battery, thereby further improving the resistance to the electrolyte or the gas generated inside the battery, and also plays a role in increasing the adhesive strength between the barrier layer 13 and the second adhesive layer 12b. The first and second corrosion prevention layers 14a and 14b can maintain the reliability of the exterior material 10 for a longer period of time. The first corrosion prevention layer 14a and the second corrosion prevention layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention treatment layers 14a, 14b (hereinafter also simply referred to as "corrosion prevention treatment layers 14a, 14b") are formed on the metal foil constituting the barrier layer 13, for example, by subjecting the metal foil to degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0037] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone, or a method using a mixture of these. In addition, it is preferable to perform a treatment using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid. This treatment not only provides a degreasing effect for aluminum, but also allows the formation of aluminum fluoride, which is a passive state, particularly when an aluminum foil is used for the barrier layer 13. Therefore, this treatment is effective in terms of corrosion resistance. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.

[0038] An example of the hydrothermal modification treatment is boehmite treatment in which an aluminum foil is immersed in boiling water containing triethanolamine. An example of the anodization treatment is alumite treatment.

[0039] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, ceria sol treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.

[0040] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. When using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.

[0041] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.

[0042] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) with excellent corrosion resistance. Therefore, a form in which a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b is obtained, so the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b only by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foils such as aluminum foils even by a general coating method.

[0043] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.

[0044] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to provide the following in the exterior packaging material 10: (1) sol dispersion stabilization, (2) improvement of adhesion to the barrier layer 13 by utilizing phosphoric acid's aluminum chelating ability, (3) imparting corrosion resistance by capturing aluminum ions (passivation formation), and (4) improvement of the cohesive force of the corrosion prevention treatment layers (oxide layers) 14a, 14b by easily causing dehydration condensation of phosphoric acid even at low temperatures.

[0045] The corrosion prevention layers 14a and 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore may lose their cohesive strength even after the drying and curing process. Therefore, it is preferable that the corrosion prevention layers 14a and 14b in this case are compounded with an anionic polymer or a cationic polymer to compensate for the cohesive strength.

[0046] The corrosion prevention treatment layers 14a, 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be formed. In addition, although it is necessary to consider the stability of the coating liquid, the corrosion prevention treatment layers 14a, 14b can be formed into a layer having both corrosion prevention function and adhesion by using a coating agent in which a rare earth element oxide sol and a polycationic polymer or a polyanionic polymer are previously mixed into a one-component solution.

[0047] The mass per unit area of ​​the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.

[0048] From the viewpoint of easily maintaining the adhesion between the sealant layer and the barrier layer, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment and contain a cationic polymer.

[0049] <Second adhesive layer 12b> The second adhesive layer 12b is a layer that bonds the barrier layer 13 and the sealant layer 16. The second adhesive layer 12b is formed using a resin composition for forming a second adhesive layer.

[0050] (Resin composition for forming second adhesive layer) The resin composition for forming the second adhesive layer includes a resin containing an acid-modified polyolefin resin, and this resin contains a halogen. The halogen is contained in the resin as a halogen atom. For example, the halogen may be contained in another polyolefin resin (hereinafter also referred to as a "halogenated polyolefin resin") contained in the resin separately from the acid-modified polyolefin resin, or may be contained in the acid-modified polyolefin resin. Hereinafter, the acid-modified polyolefin resin containing a halogen is also referred to as an "acid-modified halogenated polyolefin resin". As described above, since the resin of the resin composition for forming the second adhesive layer contains an acid-modified polyolefin resin and a halogen, the second adhesive layer 12b can have high adhesion to the barrier layer 13 and the sealant layer 16, and can impart excellent laminate strength to the exterior material 10. In addition, high seal strength can be imparted to the exterior material 10 even at high temperatures. Furthermore, since the resin of the resin composition for forming the second adhesive layer contains an acid-modified polyolefin resin and a halogen, the exterior material 10 can have excellent moisture barrier properties.

[0051] The acid-modified polyolefin resin is a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an unsaturated sulfonic acid, an acid anhydride of an unsaturated carboxylic acid, an unsaturated ester, etc. The polyolefin resin has a plurality of olefin units, and the acid-modified polyolefin resin is a polyolefin resin in which at least a portion of the plurality of olefin units is replaced with an acid-modified olefin unit. The acid-modified olefin unit is a unit in which a portion of the hydrogen atoms present in the olefin unit is replaced with an acid-modified portion provided by the unsaturated carboxylic acid derivative.

[0052] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0053] Examples of the acid anhydrides of unsaturated carboxylic acids include acid anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.

[0054] Examples of the esters of unsaturated carboxylic acids include esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconate, dimethyl tetrahydrophthalate, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate.

[0055] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0056] The acid-modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride, from the viewpoint of obtaining excellent adhesion between the barrier layer 13 and the second adhesive layer 12b. Suitable acid-modified polyolefin resins include, for example, "ADMER" manufactured by Mitsui Chemicals, Inc., "MODIC" manufactured by Mitsubishi Chemical Corporation, "TOYOTAC" manufactured by Toyobo Co., Ltd., and "SUNSTACK" manufactured by Sanyo Chemical Industries, Ltd. Such acid-modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, and this reactivity can be utilized to impart adhesion to the second adhesive layer 12b.

[0057] When the resin composition for forming the sealant layer that forms the sealant layer 16 contains a polyolefin resin as a resin, it is preferable to use a polyolefin resin similar to that polyolefin resin. For example, when the resin composition for forming the sealant layer contains polypropylene as a resin, the polyolefin of the acid-modified polyolefin resin of the resin composition for forming the second adhesive layer is preferably polypropylene. In this case, the second adhesive layer 12b can have high adhesion to the sealant layer 16 and can also improve the heat resistance of the exterior material 10.

[0058] A halogenated polyolefin resin is a polyolefin resin in which at least a part of a plurality of olefin units is replaced with a halogenated olefin unit. A halogenated olefin unit is an olefin unit in which a part or all of the hydrogen atoms present in the olefin unit are replaced with halogen atoms. In the halogenated olefin unit, the position of the halogen atom is not particularly limited.

[0059] The acid-modified halogenated polyolefin resin contains the above-mentioned acid-modified olefin unit and the above-mentioned halogenated olefin unit. The acid-modified halogenated polyolefin resin may contain an acid-modified halogenated olefin unit. The acid-modified halogenated olefin unit is an olefin unit having an acid-modified portion and a halogen atom. In the halogenated olefin unit, the position of the hydrogen atom substituted by the halogen atom is not particularly limited.

[0060] The halogen content in the second adhesive layer 12b may be 4% by mass or more, 12% by mass or more, 16% by mass or more, or 20% by mass or more, but the halogen content is preferably 12% by mass or more. In this case, the second adhesive layer 12b is sufficiently densified by the halogen content being 12% by mass or more, so that the moisture barrier property of the electrical storage device packaging material 10 is more sufficiently improved. The halogen content in the second adhesive layer 12b may be 40% by mass or less, 30% by mass or less, or 28% by mass or less, but is preferably 40% by mass or less. In this case, the halogen contained in the second adhesive layer 12b is not excessive, so that the molecular weight of the resin contained in the second adhesive layer 12b is sufficiently large, and the sealing strength of the electrical storage device packaging material 10 at high temperatures is sufficiently improved. In addition, the halogen content being 40% by mass or less suppresses the release of halogen from the second adhesive layer 12b to a certain extent, and when the packaging material 10 is used as a packaging material for an electrical storage device, the influence of the halogen on the battery element is suppressed.

[0061] Examples of the halogen include chlorine, bromine, fluorine, iodine, etc. In particular, when the resin contains chlorine as a halogen, good performance (moisture barrier property) can be imparted at low cost.

[0062] The resin composition for forming the second adhesive layer preferably further contains a polyfunctional isocyanate compound as a curing agent. In this case, when the second adhesive layer 12b further contains a polyfunctional isocyanate compound, the adhesion and heat resistance of the exterior material 10 are further improved. Examples of the polyfunctional isocyanate compound include diisocyanates such as tolylene diisocyanate, xylylene diisocyanate or hydrogenated products thereof, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or hydrogenated products thereof, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyhydric alcohols such as trimethylolpropane, biuret forms obtained by reacting these isocyanates with water, or isocyanurate forms (isocyanurate-type polyfunctional isocyanate compounds) which are trimers; and blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, or the like. In particular, the polyfunctional isocyanate compound preferably contains an isocyanurate (isocyanurate type compound). In this case, when the polyfunctional isocyanate compound contains an isocyanurate, the second adhesive layer 12b can have excellent adhesion and heat resistance, and the exterior material 10 can have high seal strength and heat resistance.

[0063] In addition, the second adhesive layer 12b may be formed using a curing catalyst when using the resin composition for forming the second adhesive layer. An example of the curing catalyst is dibutyltin dilaurate. By using the curing catalyst, the sealing strength of the exterior material 10 can be further improved, and the adhesion and heat resistance can be further improved, compared to when the resin composition for forming the second adhesive layer does not contain a curing catalyst.

[0064] When a corrosion prevention treatment layer 14b is provided on the barrier layer 13 and the second corrosion prevention treatment layer 14b has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, it is preferable that the resin composition for forming the second adhesive layer contains a compound (hereinafter also referred to as a "reactive compound") that is reactive with the above-mentioned polymer contained in the second corrosion prevention treatment layer 14b.

[0065] For example, when the second corrosion prevention treatment layer 14b contains a cationic polymer, the resin composition for forming the second adhesive layer contains a compound reactive with the cationic polymer. When the second corrosion prevention treatment layer 14b contains an anionic polymer, the resin composition for forming the second adhesive layer contains a compound reactive with the anionic polymer. When the second corrosion prevention treatment layer 14b contains a cationic polymer and an anionic polymer, the resin composition for forming the second adhesive layer contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the resin composition for forming the second adhesive layer does not necessarily need to contain the above two types of compounds, and may contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "having reactivity" means forming a covalent bond with the cationic polymer or the anionic polymer.

[0066] Examples of the compound reactive with cationic polymer include glycidyl compounds, compounds having carboxyl groups, and compounds having oxazoline groups. These can be used alone or in combination of two or more. The above-mentioned polyfunctional isocyanate compounds are also examples of the compound reactive with cationic polymer.

[0067] Examples of the glycidyl compound include epoxy compounds obtained by reacting glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol with epichlorohydrin; epoxy compounds obtained by reacting polyhydric alcohols such as glycerin, polyglycerin, trimethylolpropane, pentaerythritol, and sorbitol with epichlorohydrin; and epoxy compounds obtained by reacting dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid with epichlorohydrin.

[0068] Examples of the compound having a carboxy group include aliphatic carboxylic acid compounds, aromatic dicarboxylic acid compounds, and salts thereof. In addition, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid may be used.

[0069] Examples of compounds having an oxazoline group include low molecular weight compounds having two or more oxazoline units, and when a polymerizable monomer such as isopropenyloxazoline is used, copolymers of acrylic monomers such as (meth)acrylic acid, (meth)acrylic acid alkyl esters, and (meth)acrylic hydroxyalkyls can be mentioned.

[0070] The compound reactive with anionic polymers includes at least one compound selected from the group consisting of glycidyl compounds and compounds having oxazoline groups.These glycidyl compounds and compounds having oxazoline groups include the glycidyl compounds and compounds having oxazoline groups exemplified above as crosslinking agents for forming cationic polymers into crosslinked structures.Among these, glycidyl compounds are preferred because of their high reactivity with anionic polymers.

[0071] The reactive compound is preferably reactive with the acid-modified polyolefin resin (i.e., forms a covalent bond with the acid-modified polyolefin resin). This enhances adhesion to the second corrosion prevention treatment layer 14b. In addition, the modified polyolefin resin has a crosslinked structure, which further improves the solvent resistance of the exterior material 10.

[0072] The content of the reactive compound is preferably from the same amount to 10 times the equivalent amount of the acidic group in the acid-modified polyolefin resin. If the content of the reactive compound is equal to or more than the same amount, the reactive compound will react sufficiently with the acidic group in the acid-modified polyolefin resin. On the other hand, if the content of the reactive compound is 10 times or less, unreacted substances are unlikely to exist in the crosslinking reaction between the acid-modified polyolefin resin and the reactive compound, and various performances are unlikely to deteriorate. Therefore, for example, the content of the reactive compound is preferably 5 to 20 parts by mass (solid content ratio) per 100 parts by mass of the acid-modified polyolefin resin.

[0073] The resin composition for forming the second adhesive layer may further contain various additives such as a flame retardant, an antioxidant, a light stabilizer, a tackifier, a dehydrating agent, and a crystal nucleating agent, as necessary.

[0074] The thickness of the second adhesive layer 12b is not particularly limited, but is preferably 0.05 to 30 μm. In this case, sufficient adhesion can be obtained compared to when the thickness of the second adhesive layer 12b is less than 0.05 μm. Furthermore, the volumetric energy density of the electricity storage device can be further increased compared to when the thickness of the second adhesive layer 12b exceeds 30 μm. Furthermore, the thickness of the second adhesive layer 12b is more preferably 0.1 to 10 μm.

[0075] <Sealant layer 16> The sealant layer 16 is a layer that imparts heat-sealing sealability to the exterior material 10, and is a layer that is placed on the inside and heat-sealed (thermally fused) when assembling the electricity storage device. The sealant layer 16 may be either a single-layer film or a multi-layer film.

[0076] (Resin composition for forming sealant layer) The resin contained in the resin composition for forming the sealant layer may be a resin film made of a polyolefin resin or a polyester resin. The resin constituting the sealant layer 16 (hereinafter also referred to as "base resin") may be used alone or in combination of two or more kinds.

[0077] Examples of polyolefin resins include polyethylenes such as low-density polyethylene (LDPE or LLDPE), medium-density polyethylene, and high-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block polypropylene, and random polypropylene; block or random copolymers containing propylene as a copolymerization component; polybutene; and propylene-α-olefin copolymers. From the viewpoints of heat resistance and flexibility, the polyolefin resin is preferably polypropylene, and more preferably block polypropylene.

[0078] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof.

[0079] The resin may contain a polyolefin-based elastomer. The polyolefin-based elastomer may be compatible with the above-mentioned base resin or may not be compatible with it, but may contain both a compatible polyolefin-based elastomer that is compatible and a non-compatible polyolefin-based elastomer that is not compatible with it. Being compatible (compatible system) means that the dispersed phase has a size of 1 nm or more and less than 500 nm dispersed in the base resin. Not being compatible (non-compatible system) means that the dispersed phase has a size of 500 nm or more and less than 20 μm dispersed in the base resin.

[0080] When the base resin is a polypropylene resin, the compatible polyolefin elastomer may be, for example, a propylene-butene-1 random copolymer, and the incompatible polyolefin elastomer may be, for example, an ethylene-butene-1 random copolymer. The polyolefin elastomers may be used alone or in combination of two or more.

[0081] The resin preferably further contains a modified polyolefin resin, which allows the sealant layer 16 to have high adhesion to the second adhesive layer 12b, thereby improving the laminate strength of the exterior packaging material 10. Examples of the modified polyolefin resin include hydroxyl-modified polyolefin resin, glycidyl-modified polyolefin resin, and acid-modified polyolefin resin, etc. Among these, acid-modified polyolefin resin is preferred. The acid-modified polyolefin resin is a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an unsaturated sulfonic acid, an acid anhydride of an unsaturated carboxylic acid, an unsaturated ester, or the like.

[0082] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0083] Examples of the acid anhydrides of unsaturated carboxylic acids include acid anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.

[0084] Examples of the esters of unsaturated carboxylic acids include esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconate, dimethyl tetrahydrophthalate, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate.

[0085] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0086] From the viewpoint of obtaining excellent adhesion between the second adhesive layer 12b and the sealant layer 16, the acid-modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. Suitable modified polyolefin resins include, for example, "ADMER" manufactured by Mitsui Chemicals, Inc., "MODIC" manufactured by Mitsubishi Chemical Corporation, "TOYOTAC" manufactured by Toyobo Co., Ltd., and "SUNSTACK" manufactured by Sanyo Chemical Industries, Ltd. Such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, and therefore, the reactivity can be utilized to impart adhesion to the sealant layer 16. As the polyolefin of the acid-modified polyolefin resin, when an acid-modified polyolefin resin is used in the resin composition for forming the second adhesive layer that forms the second adhesive layer 12b, it is preferable to use a polyolefin similar to the polyolefin of the acid-modified polyolefin resin. For example, when the resin composition for forming the second adhesive layer 12b contains acid-modified polypropylene, the acid-modified polyolefin resin in the resin composition for forming the sealant layer that forms the sealant layer 16 is preferably acid-modified polypropylene. In this case, the sealant layer 16 can have high adhesion to the second adhesive layer 12b, and the heat resistance of the exterior material 10 can also be improved.

[0087] Furthermore, the sealant layer 16 may contain, as additive components, for example, slip agents, antiblocking agents, antioxidants, light stabilizers, flame retardants, dehydrating agents, tackifiers, crystal nucleating agents, etc. The content of these additive components is preferably 5 parts by mass or less, assuming that the total mass of the sealant layer 16 is 100 parts by mass.

[0088] The thickness of the sealant layer 16 is not particularly limited, but is preferably in the range of 20 to 150 μm, more preferably in the range of 30 to 150 μm, and further preferably in the range of 40 to 100 μm. When the thickness of the sealant layer 16 is 20 μm or more, the sealing strength of the exterior material 10 is further improved. When the thickness of the sealant layer 16 is 150 μm or less, the volumetric energy density of the electricity storage device can be further increased.

[0089] FIG. 1 shows an exterior material in which a barrier layer 13 is bonded to a base layer 11 via a first adhesive layer 12a, but the exterior material may also be an exterior material in which the barrier layer 13 is laminated directly on the base layer 11.

[0090] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.

[0091] The manufacturing method of the exterior material 10 of this embodiment is roughly composed of a step of providing corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using a first adhesive layer 12a, a step of further laminating a sealant layer 16 via a second adhesive layer 12b to produce a laminate, and a step of, if necessary, subjecting the obtained laminate to an aging treatment.

[0092] (Laminating process of corrosion prevention treatment layers 14a, 14b on barrier layer 13) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the barrier layer 13. As described above, examples of the method include subjecting the barrier layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.

[0093] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multi-layered, the corrosion prevention treatment layers 14a, 14b can be formed, for example, by applying a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (barrier layer 13 side) to the barrier layer 13 and baking it to form a first layer, and then applying a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer to the first layer and baking it to form a second layer, and repeating this process.

[0094] The degreasing treatment can be carried out by a spray method or a dipping method. The hydrothermal conversion treatment and the anodizing treatment can be carried out by a dipping method. The chemical conversion treatment can be carried out by appropriately selecting a method such as a dipping method, a spray method, or a coating method according to the type of chemical conversion treatment.

[0095] Regarding the method for applying the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.

[0096] As described above, the various treatments may be performed on either one or both sides of the metal foil constituting the barrier layer 13, but in the case of one-sided treatment, the treated side is preferably the side on which the sealant layer 16 is laminated. If required, the surface of the base layer 11 may also be subjected to the above treatments.

[0097] The coating amount of the coating agent for forming the first layer and the second layer is 0.005 to 0.200 g / m 2 , or 0.010 to 0.100 g / m 2 may be also possible.

[0098] Furthermore, when dry curing is required, the drying can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.

[0099] (Step of bonding the base layer 11 and the barrier layer 13) This step is a step of bonding the barrier layer 13 provided with the corrosion prevention treatment layers 14a, 14b to the base material layer 11 via the first adhesive layer 12a. Examples of the bonding method include a method of bonding the two layers using the material constituting the first adhesive layer 12a described above, using techniques such as dry lamination, non-solvent lamination, and wet lamination. The first adhesive layer 12a has a dry coating amount of 1 to 10 g / m. 2 or 2 to 7 g / m 2 It may be set in the range.

[0100] (Laminating step of second adhesive layer 12b and sealant layer 16) This step is a step of bonding the sealant layer 16 via the second adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 13. Examples of the bonding method include wet lamination and dry lamination.

[0101] For example, when the sealant layer 16 is bonded by dry lamination, the resin composition for forming the second adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, and the solvent is removed and dried at a predetermined temperature, and then the sealant layer 16 is laminated. Examples of the application method of the resin composition for forming the second adhesive layer include the various application methods exemplified above. The preferred dry application amount of the resin composition for forming the second adhesive layer is the same as that of the resin composition for forming the first adhesive layer 12a.

[0102] The resin composition for forming the second adhesive layer can be obtained by dissolving or dispersing an acid-modified halogenated polyolefin resin, or by dissolving or dispersing an acid-modified polyolefin resin and a halogenated polyolefin resin in a solvent.

[0103] The sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a T-die, using the above-mentioned resin composition for forming the sealant layer for forming the sealant layer 16. In the melt extrusion molding machine, the processing speed can be set to 80 m / min or more from the viewpoint of productivity.

[0104] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the barrier layer 13 / the second corrosion prevention treatment layer 14b / the second adhesive layer 12b / the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100° C. The aging time is, for example, 1 to 10 days.

[0105] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.

[0106] [Electricity storage device] Next, a power storage device according to an embodiment of the present disclosure will be described with reference to Fig. 2. Fig. 2 is a perspective view of the power storage device according to an embodiment of the present disclosure. 2, the power storage device 50 includes a battery element 52 and an exterior bag 54 that houses the battery element 52. The power storage device 50 may further include two metal terminals (current extraction terminals) 53 extending from the battery element 52 and for extracting current to the outside. Here, the exterior bag 54 holds the metal terminals 53. Furthermore, the exterior bag 54 may house the battery element 52 in an airtight state.

[0107] The exterior bag 54 has an exterior material 10. In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. As shown in Fig. 2, the exterior bag 54 may be formed by folding one exterior material 10 in half and heat-sealing the peripheral parts so that the base material layer 11 is on the outer side of the electricity storage device 50 and the sealant layer 16 is on the inner side of the electricity storage device 50, but it may also be formed by stacking two exterior materials 10 and heat-sealing the peripheral parts. The metal terminal 53 is sandwiched and sealed by an exterior bag 54 that forms a container with the sealant layer 16 on the inside. The metal terminal 53 may be sandwiched by the exterior material 10 via a tab sealant.

[0108] According to the electricity storage device 50, the exterior material 10 has excellent moisture barrier properties. This prevents moisture from entering the interior of the exterior bag 54, and the battery element 52 is less likely to be exposed to moisture, making it possible to prevent a decrease in performance of the battery element 52 housed inside the exterior bag 54. In addition, the exterior material 10 has excellent lamination strength and high seal strength even at high temperatures, so that even when the electricity storage device 50 is used at high temperatures, the exterior bag 54 is less likely to be damaged and a decrease in the sealing property of the exterior bag 54 can be prevented. As a result, the life of the electricity storage device 50 can be extended.

[0109] The battery element 52 includes a positive electrode, a negative electrode, and an electrolyte disposed between at least the positive electrode and the negative electrode. The electrolyte may be a liquid electrolyte or a solid electrolyte, and examples of the solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.

[0110] The electricity storage device 50 is particularly useful when the solid electrolyte is a sulfide-based solid electrolyte. In this case, the moisture barrier property of the exterior material 10 can be improved, so that the intrusion of moisture into the interior of the exterior bag 54 can be suppressed. Therefore, the generation of hydrogen sulfide due to the reaction between sulfur in the sulfide solid electrolyte and moisture can be suppressed.

[0111] Metal terminal 53 is a part of the current collector taken out from exterior material 10, and is made of metal foil such as copper foil or aluminum foil. In addition, in the electricity storage device 50, the exterior packaging material 20 may be used in place of the exterior packaging material 10. EXAMPLES

[0112] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.

[0113] [Materials used] The materials used in the examples and comparative examples are shown below. <Base layer (thickness 25 μm)> A polyethylene terephthalate (PET) film (manufactured by Unitika Ltd.) was used.

[0114] <Resin composition for forming first adhesive layer> As the resin composition for forming the first adhesive layer, a polyurethane adhesive (manufactured by Toyo Ink Co., Ltd.) containing a polyester polyol-based base agent and an adduct-based curing agent of tolylene diisocyanate was used.

[0115] <Materials for forming the first corrosion prevention treatment layer (base layer side) and the second corrosion prevention treatment layer (sealant layer side)> As materials for forming the first corrosion prevention treatment layer (base layer side) and the second corrosion prevention treatment layer (sealant layer side), the following (CL-1) and (CL-2) were used. (CL-1): "Sodium polyphosphate stabilized cerium oxide sol" obtained by using distilled water as a solvent and adjusting the solid concentration to 10% by mass. The sodium polyphosphate-stabilized cerium oxide sol was obtained by mixing 10 parts by mass of sodium phosphoric acid with 100 parts by mass of cerium oxide. (CL-2): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nittobo Co., Ltd.)" and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" obtained by adjusting the solid content concentration to 5% by mass using distilled water as a solvent.

[0116] <Barrier layer (thickness 40 μm)> Annealed and degreased soft aluminum foil (manufactured by Toyo Aluminum Co., Ltd., product name "8079 material") was used.

[0117] <Resin composition for forming second adhesive layer> (1) Resin composition A for forming the second adhesive layer The second adhesive layer-forming resin composition A was prepared as follows. That is, the following acid-modified chlorinated polyolefin resin A was dissolved in a solvent consisting of methylcyclohexane and methyl ethyl ketone, and the following polyfunctional isocyanate compound-containing liquid and curing catalyst were added to prepare the resin. (Acid-modified chlorinated polyolefin resin A) Nippon Paper Industries Co., Ltd., Product name: 3228S, Acid-modified chlorinated polyolefin resin (base material): Maleic anhydride-modified polypropylene (chlorine content: 28% by mass) (Liquid containing polyfunctional isocyanate compound) Manufactured by Tosoh Corporation, product name: Coronate HXR, multifunctional isocyanate compound (curing agent): hexamethylene diisocyanate (HDI) polyisocyanurate resin (curing catalyst) Dibutyltin dilaurate (Tokyo Chemical Industry Co., Ltd.) In addition, in the resin composition A for forming the second adhesive layer, the mass ratio of the solid contents of the acid-modified chlorinated polyolefin resin, the polyfunctional isocyanate compound and the curing catalyst was 100:0.95:0.05, and the solid content concentration was 10 mass%. (2) Resin composition B for forming the second adhesive layer Resin composition B for forming a second adhesive layer was prepared in the same manner as resin composition A for forming a second adhesive layer, except that acid-modified chlorinated polyolefin resin B described below was used instead of acid-modified chlorinated polyolefin resin A. (Acid-modified chlorinated polyolefin resin B) Nippon Paper Industries Co., Ltd., Product name: 3221S, Acid-modified chlorinated polyolefin: Maleic anhydride-modified polypropylene (chlorine content: 21% by mass) (3) Resin composition C for forming the second adhesive layer Resin composition C for forming a second adhesive layer was prepared in the same manner as resin composition A for forming a second adhesive layer, except that a mixture of acid-modified chlorinated polyolefin resin C and a chlorinated polyolefin resin described below was used instead of acid-modified chlorinated polyolefin resin A, and the chlorine content in the solid content of the mixture was 20 mass%. (Acid-modified polyolefin resin C) Nippon Paper Industries Co., Ltd., product name 150S, acid-modified polyolefin resin: maleic anhydride-modified polypropylene (chlorine content: 0% by mass) (Chlorinated polyolefin resin) Nippon Paper Industries Co., Ltd., product name 390S, chlorinated polyolefin resin: chlorinated polypropylene (chlorine content: 36% by mass) (4) Resin composition D for forming second adhesive layer Resin composition D for forming a second adhesive layer was prepared in the same manner as resin composition A for forming a second adhesive layer, except that a mixture of the above-mentioned acid-modified chlorinated polyolefin resin C and a chlorinated polyolefin resin was used instead of acid-modified chlorinated polyolefin resin A, and the chlorine content in the solid content of the mixture was 12 mass%. (5) Resin composition E for forming second adhesive layer Resin composition D for forming a second adhesive layer was prepared in the same manner as resin composition A for forming a second adhesive layer, except that a mixture of the above-mentioned acid-modified chlorinated polyolefin resin C and a chlorinated polyolefin resin was used instead of acid-modified chlorinated polyolefin resin A, and the chlorine content in the solid content of the mixture was 4 mass%. (6) Resin composition F for forming second adhesive layer Resin composition F for forming a second adhesive layer was prepared in the same manner as resin composition A for forming a second adhesive layer, except that the above-mentioned acid-modified polyolefin resin C was used instead of acid-modified chlorinated polyolefin resin A, and the chlorine content in the solid content of the mixture was 0 mass%. (7) Resin composition G for forming second adhesive layer The acid-modified polyolefin resin C, the layered compound filler described below, the polyfunctional isocyanate compound-containing liquid, and the curing catalyst were added to a solvent consisting of methylcyclohexane and methyl ethyl ketone to prepare the solution. (Layered compound filler) Manufactured by Nippon Organic Viscosity Co., Ltd., product name: Esben NZ, quaternary ammonium modified montmorillonite, average particle size: 1 μm In the second adhesive layer-forming resin composition G, the mass ratio of the solid components, that is, the acid-modified polyolefin resin, the layered compound filler, the polyfunctional isocyanate compound, and the curing catalyst was 80:20:0.95:0.05.

[0118] <Sealant layer for dry lamination> An unstretched polypropylene film (product name: Aromar Film UT100, manufactured by Okamoto Corporation, thickness 80 μm) was used.

[0119] [Creating exterior materials] <Example 1> First, a first and a second corrosion prevention treatment layer were provided on the barrier layer by the following procedure: (CL-1) was applied on both sides of the barrier layer in a dry coating amount of 70 mg / m 2 The layer was then coated by microgravure coating so that the thickness of the layer was 200 mm, and the layer was baked at 200° C. in a drying unit. Next, (CL-2) was applied onto the layer obtained in a dry coating amount of 20 mg / m 2 By applying the coating by microgravure coating so that the above-mentioned coating conditions were satisfied, a composite layer consisting of a layer of (CL-1) and a layer of (CL-2) was formed as the first and second corrosion prevention treatment layers. This composite layer exhibits corrosion prevention performance by combining the two types of materials, (CL-1) and (CL-2).

[0120] Next, the first corrosion prevention treatment layer side of the barrier layer provided with the first and second corrosion prevention treatment layers was attached to the base layer by dry lamination using a polyurethane adhesive (a resin composition for forming a first adhesive layer). The lamination of the barrier layer and the base layer was performed by applying a polyurethane adhesive to the surface of the first corrosion prevention treatment layer opposite the barrier layer so that the thickness after curing was 5 μm, drying at 80° C. for 1 minute, laminating it with the base layer, and aging it at 60° C. for 72 hours. In this way, a first laminate including the barrier layer and the base layer was obtained.

[0121] Next, the resin composition for forming the second adhesive layer was applied to the second corrosion prevention treatment layer of the first laminate obtained as described above using a bar coater, and then dried at 100°C for 1 minute to form a second adhesive layer. After drying, the thickness of the second adhesive layer was 5 μm. Furthermore, the second adhesive layer was laminated with a sealant layer for dry lamination, and aged at 40°C for 72 hours.

[0122] In this manner, an exterior material according to Example 1 (substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / second adhesive layer / sealant layer) was produced.

[0123] Example 2 An exterior material according to Example 2 was obtained in the same manner as in Example 1, except that the resin composition B for forming the second adhesive layer was used as the resin composition for forming the second adhesive layer.

[0124] Example 3 An exterior material according to Example 3 was obtained in the same manner as in Example 1, except that the resin composition C for forming the second adhesive layer was used as the resin composition for forming the second adhesive layer.

[0125] Example 4 An exterior material according to Example 4 was obtained in the same manner as in Example 1, except that the resin composition D for forming the second adhesive layer was used as the resin composition for forming the second adhesive layer.

[0126] Example 5 An exterior material according to Example 5 was obtained in the same manner as in Example 1, except that the resin composition E for forming the second adhesive layer was used as the resin composition for forming the second adhesive layer.

[0127] Comparative Example 1 An exterior material according to Comparative Example 1 was obtained in the same manner as in Example 1, except that second adhesive layer-forming resin composition F was used as the second adhesive layer-forming resin composition.

[0128] Comparative Example 2 An exterior material according to Comparative Example 2 was obtained in the same manner as in Example 1, except that resin composition G for forming the second adhesive layer was used as the resin composition for forming the second adhesive layer.

[0129] <Evaluation> (1) Seal strength (1-1) Preparation of samples for measuring seal strength The prepared exterior material was cut into a sample measuring 50 mm (TD) x 100 mm (MD), folded in half so as to sandwich a piece of chemically treated aluminum foil cut to a size of 50 mm x 50 mm, and the end opposite the folded part was heat sealed over a width of 10 mm at 180°C, 0.6 MPa, and 10 seconds. After that, a 15 mm wide sample was cut out from the longitudinal center of the heat sealed part (see Figure 3) to prepare a sample for measuring the seal strength. (1-2) Seal strength (room temperature) The seal strength measurement samples prepared as described above were subjected to a T-peel test to peel the exterior material from the chemically treated aluminum foil at a room temperature (25°C) environment and a tensile speed of 50 mm / min using a tensile tester (manufactured by Shimadzu Corporation), thereby measuring the seal strength. (1-3) Seal strength (120℃) The seal strength measurement sample prepared as described above was left for 5 minutes in a high-temperature environment at 120° C. Thereafter, a T-peel test was performed on the seal strength measurement sample at a tensile speed of 50 mm / min using a tensile tester (manufactured by Shimadzu Corporation) to peel the exterior material from the chemically treated aluminum foil, thereby measuring the seal strength. (1-4) Rating The seal strength (burst strength) obtained in (1-2) and (1-3) above was evaluated based on the following criteria. The seal strength and evaluation results are shown in Table 1. (standard) 〇: Seal strength is 20N / 15mm or more ×: Seal strength is less than 20N / 15mm

[0130] (2) Laminate strength From the prepared exterior material, a piece of exterior material with a width of 15 mm and a length of 120 mm was cut out, and a T-peel test was performed to peel between the barrier layer and the sealant layer of the exterior material using a tensile tester (manufactured by Shimadzu Corporation) at room temperature (25°C) and a tensile speed of 50 mm / min to measure the laminate strength. The obtained laminate strength was then evaluated based on the following criteria. The laminate strength and evaluation results are shown in Table 1. (standard) 〇: Lamination strength is 15N / 15mm or more, or peeling is not possible ×: Laminate strength is less than 15N / 15mm

[0131] (3) Moisture barrier properties Two sheets of the exterior material were cut out from the prepared exterior material, and the sealant layers of the two exterior materials were placed opposite each other, and the three sides were joined by heat sealing so that the encapsulation size was 100 mm x 45 mm. 3 g of electrolyte solution not containing lithium salt was injected from the open side, and the open side was heat sealed to seal it. Then, the periphery was trimmed so that the heat seal width was 5 mm, and the product was left for one day in an environment of 40 ° C and 90% RH (relative humidity). Then, the moisture content in the encapsulated electrolyte was measured with a Karl Fischer moisture meter, and the permeated moisture content was calculated from the measured moisture content. The moisture barrier property was evaluated based on the obtained permeated moisture content based on the following criteria. The permeated moisture content and evaluation results are shown in Table 1. (standard) ◎: Permeation moisture amount is 0.050g / m 2 Less than a day ○: Permeation moisture amount is 0.050g / m 2 ·day or more 0.400g / m 2 Less than a day ×: Permeation moisture amount is 0.400g / m 2 ·day or more

[0132] [Table 1]

[0133] From the results shown in Table 1, the moisture barrier property was evaluated as "◎" or "◯" in Examples 1 to 5, whereas the moisture barrier property was evaluated as "×" in Comparative Example 1. Furthermore, the seal strength at 120°C was judged as "◯" in Examples 1 to 5, whereas the seal strength at 120°C and the laminate strength at 25°C in Comparative Example 2 were both evaluated as "×".

[0134] From the above, it was confirmed that the packaging material for an electricity storage device according to the present disclosure has excellent moisture barrier properties and lamination strength, and also has high seal strength even at high temperatures.

[0135] The outline of this disclosure is as follows. [1] A substrate layer, a barrier layer, an adhesive layer, and a sealant layer in this order; The adhesive layer is formed using a resin composition including a resin containing an acid-modified polyolefin resin, The exterior material for an electricity storage device, wherein the resin contains a halogen. [2] The exterior packaging material for a power storage device according to [1], wherein the adhesive layer has a content of the halogen of 12 mass % or more. [3] The exterior packaging material for a storage battery device according to [1] or [2], wherein the adhesive layer has a halogen content of 40 mass % or less. [4] The exterior packaging material for a power storage device according to any one of [1] to [3], wherein the resin composition contains a polyfunctional isocyanate compound. [5] The exterior packaging material for a storage battery device according to claim [4], wherein the polyfunctional isocyanate compound contains at least an isocyanurate type compound. [6] a storage element; and and an outer bag for housing the battery element; The exterior bag of the electricity storage device comprises the exterior material for a electricity storage device according to any one of [1] to [5]. [Industrial Applicability]

[0136] The exterior packaging material for an electricity storage device according to the present disclosure can achieve both improved moisture barrier properties and maintenance of adhesion in high-temperature environments, and therefore the present disclosure can be applied to electricity storage devices such as all-solid-state batteries. [Explanation of symbols]

[0137] 10...outer packaging material (outer packaging material for electricity storage device), 11...base material layer, 12b...second adhesive layer (adhesive layer), 13...barrier layer, 16...sealant layer, 50...electricity storage device, 52...battery element, 54...outer packaging bag.

Claims

1. A substrate layer, a barrier layer, an adhesive layer, and a sealant layer, in this order; The adhesive layer is formed using a resin composition including a resin containing an acid-modified polyolefin resin, The exterior material for an electricity storage device, wherein the resin contains a halogen.

2. The packaging material for a power storage device according to claim 1 , wherein a content of the halogen in the adhesive layer is 12 mass % or more.

3. The packaging material for a power storage device according to claim 2 , wherein a content of the halogen in the adhesive layer is 40 mass % or less.

4. The packaging material for an electricity storage device according to claim 1 , wherein the resin composition contains a polyfunctional isocyanate compound.

5. The packaging material for an electricity storage device according to claim 4 , wherein the polyfunctional isocyanate compound includes at least an isocyanurate compound.

6. A battery element; and an outer bag for housing the battery element; The outer bag comprises the outer packaging material for an electricity storage device according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Laminate sheet for sulfide-based all-solid-state battery and laminate pack using the same

    JP2020187855A